Dominican Republic - Environmental Priorities and Strategic Options : Country Environmental Analysis - World Bank (Washington, DC, 2013)
This report discusses the affects of rapid economic growth and increased urbanization on the environmental quality of the Dominican Republic's natural resource base (e.g., water resources management--water quality, quantity and watershed management and solid waste collection and disposal have become major environmental concerns). It notes that the lack of systematic data limits an accurate and detailed assessment of the scope of the problems, however, the consensus is that: (i) the overall poor quality of surface, groundwater and coastal water resources is the result of a lack of waste water management and agricultural run-off, causing health problems that disproportionately affect the poor; (ii) water scarcity is a regional problem resulting from poor demand management in irrigation, urban water supply and tourist infrastructure in drier regions; (iii) weak watershed management leads to soil erosion and amplifies the damage and frequency of flooding; and (4) the overall lack of solid waste management pollutes water sources, causes disease and is a nuisance for both inhabitants and visitors. To rectify these problems, the country established the Secretariat for the Environment and Natural Resources (SEMARN) in 2000, bringing all public institutions dealing with environmental issues under one roof. The World Bank has supported SEMARN through a Learning and Innovation Loan, and SEMARN has made significant progress since its inception by issuing environmental regulations, standards and impact assessment procedures, among other reforms and improvements. This report provides some indicative priority setting the Government could adopt or adjust in function of political and economic factors.